The association between high ambient air pollution exposure and respiratory health of young children: A cross sectional study in Jinan, China - Chen, Zhangjian; Cui, Liangliang; Cui, Xiaoxing; Li, Xinwei; Yu, Kunkun; Yue, Kesan; Dai, Zhixiang; Zhou, Jingwen; Jia, Guang; Zhang, Ji (The Science of the total environment, 2019)
There is growing concern about health effects of high air pollution in less-developed countries. Children represent a population at increased risk for air pollution–related respiratory conditions. This study investigated the relationship between high ambient air pollution exposure and respiratory health of young schoolchildren. From 2014 to 2016 in Jinan, China, 2532 primary school children in grades three to five from two different schools with different levels of air pollution were included in the study. Levels of ambient air pollution exposure including PM10, PM2.5, NO2, SO2, CO and O3 were measured continuously at the two schools. A questionnaire about children's respiratory health was conducted every year. Among them, about 150 randomly selected children also performed lung function tests two times a year at the beginning of November and middle of December. Annual average exposure levels of PM2.5 (66.8–79.1 vs 90.0–107.7 μg/m3), PM10 (129.5–177.3 vs 198.1–218.6 μg/m3), NO2 (45.3–53.2 vs 45.0–56.2 μg/m3), SO2 (29.8–56.5 vs 40.5–80.3 μg/m3), CO (1.3–1.5 vs 1.4–1.7 mg/m3) and O3 (84.8–120.2 vs 61.1–128.1 μg/m3) in the heavy pollution primary school were significantly higher than the light one. The higher air pollution exposure was related to increased prevalence of respiratory diseases of young children in the last year, especially allergic rhinitis. The increased odds of lung function impairment associated with exposure to higher air pollution, could be up to 171.5% (aOR = 2.715; 95% CI = 1.915–3.849) for PEF < 75% predicted in 2014. However, after short-term exposure for 1.5 month or a week, paired comparison for parameters of the same child showed different results. The association between high ambient air pollution exposure and respiratory health of young children is closely related to exposure time and dose and may be fluctuate and complex. [Display omitted] •2532 primary school children from two different schools with different levels of air pollution were included in the study.•Levels of PM10, PM2.5, NO2, SO2, CO and O3 were daily measured in two schools from 2014 to 2016.•The levels of air pollutants within our study were rather high, which could be up to 6-10 times higher than the WHO AQGs.•Annual data showed increased prevalence of respiratory diseases and lung function impairment in higher pollution school.•Exposure time and dose influenced the association between high ambient air pollution exposure and respiratory health.